Readiness to build capacity in community sport organizations. Issue 1 (4th March 2021) - Millar, Patti; Doherty, Alison
ABSTRACT: Rationale/Purpose: Capacity building as a tool to address sector-wide challenges has received increasing attention in research and practice. This study examines the strength and impact of readiness to build capacity on the outcomes of those efforts. Design/methodology/approach: Environmental stimuli, readiness for capacity building (organizational readiness, congruence, existing capacity), and capacity building outcomes were analyzed from 144 cases within community sport organizations (CSO). Findings: Results indicate that congruence of the capacity building strategy with CSOs' values and operations was the strongest indicator of readiness, followed by members' willingness and commitment, and the CSOs' existing capacity. The model of readiness significantly impacted capacity building outcomes, with existing capacity as the most impactful in achieving outcomes. Practical Implications: Given increasing demands and pressures placed on CSOs, this research highlights the importance of readiness as CSOs address environmental stimuli. Research Contribution: Understanding the impact of readiness provides theoretical clarity regarding capacity building as a strategic approach to addressing organizational challenges.